2021
DOI: 10.1111/nph.17227
|View full text |Cite
|
Sign up to set email alerts
|

Pollen sterols are associated with phylogeny and environment but not with pollinator guilds

Abstract: Phytosterols are primary plant metabolites that have fundamental structural and regulatory functions. They are also essential nutrients for phytophagous insects, including pollinators, that cannot synthesize sterols. Despite the well-described composition and diversity in vegetative plant tissues, few studies have examined phytosterol diversity in pollen. We quantified 25 pollen phytosterols in 122 plant species (105 genera, 51 families) to determine their composition and diversity across plant taxa. We search… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 88 publications
0
40
0
Order By: Relevance
“…However, bees need to obtain these nutrients in appropriate quantities and ratios to best support their development, fitness and health [62][63][64], as shown for the bumblebees Bombus terrestris and B. impatiens that select and perform best on pollen diets with high protein to fat ratios and a generally low fat content [65][66][67]. In nature, amounts and composition of nutrients in pollen vary strongly between plant species [49,51,[68][69][70], which may explain why bees are much more selective when foraging for pollen than nectar [71]. However, the interaction between microbes and nutrients in pollen, and consequences for bees, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, bees need to obtain these nutrients in appropriate quantities and ratios to best support their development, fitness and health [62][63][64], as shown for the bumblebees Bombus terrestris and B. impatiens that select and perform best on pollen diets with high protein to fat ratios and a generally low fat content [65][66][67]. In nature, amounts and composition of nutrients in pollen vary strongly between plant species [49,51,[68][69][70], which may explain why bees are much more selective when foraging for pollen than nectar [71]. However, the interaction between microbes and nutrients in pollen, and consequences for bees, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in analytical methods facilitate accurate quantitative chemical analysis of pollen, including fatty acids and protein-bound and free amino acids [97], sterols [98][99][100], plant secondary metabolites [101], and chemical elements [89]. The chemical/nutritional profile of the overall pollen diet of a bee individual can thus be calculated by integrating information on the proportional contributions of the nutritional profiles of pollen of all plant species visited for pollen collection (e.g., obtained through metabarcoding or palynological studies).…”
Section: Trends In Ecology and Evolutionmentioning
confidence: 99%
“…These are mostly specialized bees that forage on multiple different Asteraceae species, whereas generalist bee species avoid Asteraceae pollen despite the ubiquitous distribution of this plant family and the substantial amount of pollen provision (known as the Asteraceae paradox [105]). Although the reasons for this paradox remain unresolved, the abundance of specific chemical compounds (e.g., Δ7-sterols) in the pollen of Asteraceae species may offer an explanation [100].…”
Section: Trends In Ecology and Evolutionmentioning
confidence: 99%
“…A detailed chemical profile of S. cereale pollen is, to the best of our knowledge, not available in scientific literature. Pollen is typically composed of carbohydrates, amino acids, proteins, phenolic compounds, sterols, triglycerides, plant pigments, such as carotenoids and flavonoids, minerals and sporopollenin [ 103 , 104 , 105 , 218 ] ( Table 2 ). A standardized mixture of pollen of S. cereale (92%), Phleum pratense (timothy; 5%) and Zea mays (corn; 3%) branded as Graminex [ 106 ] has been studied by Locatelli et al [ 219 ], and carvacrol, a monoterpenoid, was identified as the predominant phenolic compound, followed by polyphenols quercetin, rutin, chlorogenic acid and gallic acid [ 219 ].…”
Section: Medicinal Plants Widely Used In the Treatment Of Bphmentioning
confidence: 99%